Glycomic characterization of respiratory tract tissues of ferrets: Implications for its use in influenza virus infection studies - Roberts, Kim (My University, 2014)
The initial recognition between influenza virus and the host cell is mediated by interactions between the viral surface protein hemagglutinin and sialic acid-terminated glycoconjugates on the host cell surface. The sialic acid residues can be linked to the adjacent monosaccharide by [alpha]2–3- or [alpha]2–6-type glycosidic bonds. It is this linkage difference that primarily defines the species barrier of the influenza virus infection with [alpha]2–3 binding being associated with avian influenza viruses and [alpha]2–6 binding being associated with human strains. The ferret has been extensively used as an animal model to study the transmission of influenza. To better understand the validity of this model system, we undertook glycomic characterization of respiratory tissues of ferret, which allows a comparison of potential viral receptors to be made between humans and ferrets. To complement the structural analysis, lectin staining experiments were performed to characterize the regional distributions of glycans along the respiratory tract of ferrets. Finally, the binding between the glycans identified and the hemagglutinins of different strains of influenza viruses was assessed by glycan array experiments. Our data indicated that the respiratory tissues of ferret heterogeneously express both [alpha]2–3- and [alpha]2–6-linked sialic acids. However, the respiratory tissues of ferret also expressed the Sda epitope (NeuAc [alpha]23(GalNAc[alpha]1–4)Gal[alpha]1–4GlcNAc) and sialylated N,N[alpha]-diacetyllactosamine (NeuAc[alpha]2–6GalNAc[alpha]1–4GlcNAc), which have not been observed in the human respiratory tract surface epithelium. The presence of the Sda epitope reduces potential binding sites for avian viruses and thus may have implications for the usefulness of the ferret in the study of influenza virus infection.
PUBLISHED
Keywords: influenza viruses; ferrets